Mapping Genetic Associations With Functional Brain Area Alterations in Schizophrenia and Implications for Cortical Development - Jun‐Ding Zhu; Chih‐Yun Chung; Shu‐Fei Lin; Shih‐Jen Tsai; Albert C. Yang; Pei‐Shan Hou (Brain and Behavior)
ABSTRACT Background While prior studies have identified regional reduction in gray matter (GM) volume in schizophrenia, it remains unclear whether these alterations are concentrated in specific brain functional areas and how they relate to genetic factors. This study aimed to identify Brodmann's areas (BAs) with affected GM volume in individuals with schizophrenia, explore associated genetic variants through a genome‐wide association study (GWAS), and investigate the potential roles of these genes during cortical development. Methods The study recruited 194 individuals with schizophrenia and 330 healthy controls from the Taiwan Aging Mental Illness cohort. T1‐weighted MRI scans were processed to assess GM volume changes, and the cerebral cortex was parcellated into BAs for detailed analysis. GWAS was conducted to identify schizophrenia‐associated genetic variants, followed by functional mapping, single‐cell RNA sequencing analysis of developing human cortical cells, and in situ hybridization analysis in the developing mouse neocortex. Results Significant reductions in GM volume were found in specific BAs, particularly in the ventral frontal cortex, anterior temporal lobe, and cingulate cortex, with BA13, BA23, BA24, BA25, BA27, BA28, BA31, BA34, BA35, and BA38 showing the most pronounced changes. GWAS identified multiple genetic variants associated with these affected BAs. Further, single‐cell RNA sequencing and in situ hybridization analyses revealed dynamic expression patterns of the schizophrenia‐associated genes during cortical development, suggesting their potential roles in the structural abnormalities observed in schizophrenia. Conclusions The findings support the hypothesis that specific BAs are more vulnerable to GM volume reduction in schizophrenia, potentially driven by distinct genetic factors.